Genome sequencing and annotation of Stenotrophomonas sp. SAM8 - Selim, Samy (Genom Data, 2015)
We report draft genome sequence of Stenotrophomonas sp. strain SAM8, isolated from environmental water. The draft genome size is 3,665,538 bp with a G + C content of 67.2% and contains 6 rRNA sequence (single copies of 5S, 16S & 23S rRNA). The genome sequence can be accessed at DDBJ/EMBL/GenBank under the accession no. LDAV00000000.